A Novel Model for Evaluating the Natural Antioxidant Carnosic Acid to Improve the Stability of Rapeseed Oil in the Thermal Degradation - Yingdan Zhu; Chengliang Chai; Yalin Xue; Yong Wang; Zhangqun Duan (MDPI AG, 2024)
The quality and stability of oil during thermal processing reflect the reactions in vegetable oil. The deterioration of the oil is close to the viscosity, fatty acid composition (FA), total polar compounds (TPC), etc. Carnosic acid (CA) is the main antioxidant component of rosemary extract; it is a natural and clean-label antioxidant that is allowed to be added to prolong oil processing and storage. To achieve a clear correlation of this situation, a novel stability evaluation model was used to predict the thermal degradation of rapeseed oil (RSO) with CA. The RSO with CA (200 mg/kg, 400 mg/kg, and 700 mg/kg), the tert-Butylhydroquinone (TBHQ, 200 mg/kg), and the fresh RSO (without additives) during thermal processing (180 ± 5 °C) were studied. The temperature dependency of viscosity fits well with the Lioumbas model (R2 ≥ 0.999). The parameter b value in the Lioumbas model showed a decrease linearly with the processing time (tP, R2 ≥ 0.965). The multiple linear regression analysis showed that the accuracy of the model in predicting viscosity was less than ±2 mPa·s−1, and the deviation% was less than ±10% in all the samples. After 32 h of thermal degradation, the addition of 700 mg/kg CA showed the lowest degradation rate (13.84%) of polyunsaturated fatty acids (PUFAs), and the TPC content was 26.00 ± 0.50%. The TPC showed a positive relationship with viscosity (r = 0.99, p < 0.01), tP (r = 0.97, p < 0.01), and effective carbon numbers (ECN, r = 0.84, p < 0.05). In conclusion, this study can make a potential prediction for the stability of RSO.